(untitled) - McCuen, Richard H. (Upper Saddle River, New Jersey, 1998)
The book provides an introduction to engineering design methods. It includes peak discharge, hydrograph, and design-storm computer methods. It discusses the hydrologic cycle, with emphasis placed on small watershed design, urban hydrology, and stromwater management
Keywords: Hydraulic engineering,Hydrology